Incidental Radiologic Findings in the 22q11.2 Deletion Syndrome - Schmitt, J.E.; Yi, J.J.; Roalf, D.R.; Loevner, L.A.; Ruparel, K.; Whinna, D.; Souders, M.C.; McDonald-McGinn, D.M.; Yodh, E.; Vandekar, S.; Zackai, E.H.; Gur, R.C.; et al. (American Journal of Neuroradiology, 2014)
BACKGROUND AND PURPOSE: The 22q11.2 deletion syndrome is a common genetic microdeletion syndrome that results in cognitive delays and an increased risk of several psychiatric disorders, particularly schizophrenia. The current study investigates the prevalence of incidental neuroradiologic findings within this population and their relationships with psychiatric conditions. MATERIALS AND METHODS: Brain MR imaging from 58 individuals with 22q11.2 deletion syndrome was reviewed by board-certified radiologists by using standard clinical procedures. Intracranial incidental findings were classified into 8 categories and compared with a large typically developing cohort. RESULTS: The rate of incidental findings was significantly higher (P < .0001) in 22q11.2 deletion syndrome compared with typically developing individuals, driven by a high prevalence of cavum septum pellucidum (19.0%) and white matter abnormalities (10.3%). Both of these findings were associated with psychosis in 22q11.2 deletion syndrome. CONCLUSIONS: Cavum septum pellucidum and white matter hyperintensities are significantly more prevalent in patients with the 22q11.2 deletion syndrome and may represent biomarkers for psychosis. CSPcavum septum pellucidumPNCPhiladelphia Neurodevelopmental Cohort22q11DS22q11.2 deletion syndromeTDtypically developing